2018
DOI: 10.17235/reed.2018.5323/2017
|View full text |Cite
|
Sign up to set email alerts
|

Self-expandable metal stents are a valid option in long-term survivors of advanced esophageal cancer

Abstract: AUTHOR CONTRIBUTIONSDr. Rodrigues-Pinto was responsible for the study concept and design, data acquisition, analysis and interpretation of data, statistical analysis, drafting and writing of the paper. The remaining authors participated in a critical revision of the manuscript for important intellectual content. ABSTRACTBackground: self-expandable metal stents are often used for the palliative treatment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(16 reference statements)
0
3
0
1
Order By: Relevance
“…Re-obstruction due to ingrowth ranges between 17 and 36% for uncovered stents and is uncommon for covered stents [ 2 , 3 , 16 ]. Adverse events, including tumour overgrowth, may occur in up to 60% of the patients who are followed up for long periods [ 3 , 31 ].…”
Section: Oesophageal Stentingmentioning
confidence: 99%
“…Re-obstruction due to ingrowth ranges between 17 and 36% for uncovered stents and is uncommon for covered stents [ 2 , 3 , 16 ]. Adverse events, including tumour overgrowth, may occur in up to 60% of the patients who are followed up for long periods [ 3 , 31 ].…”
Section: Oesophageal Stentingmentioning
confidence: 99%
“…Stent placement into the esophagus has been used widely because of its rapid improvement of dysphagia, and is the most common treatment for NEAS ( 1 , 29 ). Pinto and colleagues ( 30 ) reported that in the palliative treatment of patients with advanced esophageal cancer, the patency duration of an esophageal stent in 42 patients was 236 days, and that the clinical symptoms of all patients were improved. However, implantation of a simple stent into the esophagus only temporarily solves the problem of an esophagogastric anastomotic stricture and does not treat the primary disease.…”
Section: Discussionmentioning
confidence: 99%
“…Some retrospective cohorts evaluated patients submitted to SEMS placement, with ≥6-month survival, and concluded that SEMS may be a valid alternative, especially in centers where brachytherapy is not widely available. Despite the increased risk of AEs over time, most of them can be managed endoscopically [ 20 , 21 , 22 ].…”
Section: Esophageal Stentingmentioning
confidence: 99%
“…GE Port J Gastroenterol 2023;30(suppl 1):[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] …”
unclassified